Developing Talent – a unique way to business: A study of Talent Management with reference to ‘People Analytics’ practiced by Google - Booshan, Shabista (International Journal of Scientific Research and Management (IJSRM), 2017)
Devising a unique HR mechanism to ensure the stability of the employees as well as growth of the company is the need of this hour. But how many companies do we know who are really indulging in this kind of a practice or at least are devising something new in this area of concern. It takes fraction of a second for me to relate the TV commercial of Naukari.com. The very famous advertisement of HariSadu…that claims loudly that if you are caught in a wrong job the next thing is to quit the job and take up another one where you fit the bill. Yes ‘fit the bill’ probably should be the mantra in today’s time for all the HR practitioners. The HR team must make sure that either the candidate hired, already possesses the matching quality of the position given to him or else the existing employees must be given appropriate training to be on par with the requirement of the position. In any given case the JD and the skill of the hired employee must match and only then can any company can achieve its goal and growth. Unlike olden days of where there used to be a huge gap between the management and the laborers or employees today CEOs and senior-level executives make an effort to know employees personally, and they often participate in onboarding, training, recognition and company celebrations. When employee and employer values and visions align, we see companies succeeding, followed by effective productivity and innovation. These are the few best practices that some of the best companies to work with have taken up. One of the top in the list is Google. Always looking to increase productivity and reduce overhead, companies from various industries are turning to this big datadriven approach, and Google is leading the charge. When it comes to best practices Google is famed for not only it’s one of the most unique feature/service of search engine but it is also illustrious since this is the only company that has a unique HR function on the planet that is managed based on “people analytics”